Risking relegation or staying in the first league? industrial relations and enterprise restructuring in Germany under the impact of globalisation and financialisation. (1st April 2008) - Jürgen Kädtler,
Abstract : The 'dual system' of industrial relations has formed a crucial component of the 'German Model' of post war capitalism. However it has come under severe pressure since the ending of the 'Golden Age' of Fordism and both nations and companies have been forced to engage with the new demands of globalisation. The focus of this article is on one important aspect of this development: the impact of organisational globalisation in large companies on industrial relations and on employees' bargaining power, drawing on research in the German chemical, pharmaceutical and automotive industries. It is argued that whether employees' primary power will erode, persist, or even increase depends critically on companies' product strategies. The article draws attention to ways in which employees' bargaining positions may be eroded either because the traditional strategies of unions and works councils make it difficult to draw on primary power at a local level or because primary power is shifting to new groups of employees who were traditionally not well organised. However it also points to some ways in which bargaining has been successful under these new circumstances.